The level of Post-Traumatic Stress Disorder among the displaced adolescents Field Study in Mesyaf (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research aims to solve one of the most complex issues of sociology of development and social change, not to mention the dismantling of one of the most important issues of sociology and sociology of culture. The issue of capitalist globalization and its historical stages of development, as well as the question of whether, especially at its new stage of development, it is a global system or global anarchy? Capitalism, by its structural logic, is not an antistatic system; it is a dynamic system open to shifting and shifting historical horizons. They have been deported at various stages, to a large extent, at the level of form or appearance, although they remain captive to content and one structural logic. As such, in the light of the recent results of the research, we have called for serious action to build a truly new world order based on the rules of pluralism, justice and democracy, as another system replacing the world order based on unilateralism, hegemony and dictatorship.